2018
DOI: 10.1089/pop.2017.0030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Frequent Emergency Department Use Among Primary Care Patients

Abstract: Patients with high emergency department (ED) utilization are an important focus in population health management. This retrospective cohort study analyzed patterns of frequent ED use for 4087 patients enrolled at an academically-affiliated primary care clinic. For all ED visits (n = 4776), the chief complaints, admission rates, number of complaints per patient, and median time between return visits were assessed. Chart reviews were conducted for the 10 highest utilizers from each of the 3 leading complaints to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 21 publications
5
42
1
Order By: Relevance
“…The majority of FEDU had 4 to 10 visits in 1 year, but 5% of FEDU reported to have 21 or more ED visits . The mean number of ED visits across studies was 6.6 to 8.7 visits . Studies that used higher thresholds for FEDU (≥10 or ≥12 ED visits in the past 12 months) found that FEDU had a mean of 19 and 17 ED visits in the previous 12 months, respectively .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The majority of FEDU had 4 to 10 visits in 1 year, but 5% of FEDU reported to have 21 or more ED visits . The mean number of ED visits across studies was 6.6 to 8.7 visits . Studies that used higher thresholds for FEDU (≥10 or ≥12 ED visits in the past 12 months) found that FEDU had a mean of 19 and 17 ED visits in the previous 12 months, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…We identified four sources of bias within studies related to (1) strategies to deal with confounding variables (eg, selective reporting of results for studies that did not deal with confounding variables), (2) failure to use proper statistical methods, (3) sample size, or (4) valid and reliable measurement of outcomes (eg, response and recall bias for survey‐based results) (Figure ) 21‐31. The risk of bias across studies was low, since we extracted most information from studies with low risk of bias…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 , 45 This may be particularly relevant to patients with multiple chronic illnesses, who often have fewer personal resources but utilize more services overall (ED and non-ED), compared with those without chronic illnesses. 43 , 46 - 48 Although patients with multiple co-morbidities are more likely to report having non-ED USOC providers, management of their chronic diseases may be suboptimal; as such, there are increased calls to provide more patient-centered primary care to coordinate services for high-risk populations. 14 - 17 , 47 The availability of “one-stop shopping” at the ED, which may exemplify high quality for patients who associate “more” with “better” health care, and the successes of hospitals’ continuous quality improvement initiatives 30 may also confound efforts to differentiate the value proposition of primary versus ED care for safety-net patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its management answers a humanistic, ethical, and human dignity objective because of the numerous physical and psychological repercussions [ 3 ]. Pain is one of the main symptoms motivating patients to consult in emergency settings [ 4 ], and are the leading complaints and the leading sources of hospital admissions and repeat visits [ 5 ]. However, in Emergency Departments (ED), it is underestimated and insufficiently treated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%